Information System Using Website In Letter Archiving System Design - Badawi, Afif; Mayasari, Nova; Ismail, Reza (Bahasa Indonesia, 2024)
This study aims to design and develop a website-based information system for managing letter archives in an organization. The problem faced is the lack of efficiency in manual letter archive management, which often causes data loss, delays in access, and the inability to track incoming and outgoing letters quickly. Therefore, a system is needed that is able to automate the letter archiving process and facilitate fast and accurate search for archive data. The research method used in this study is the system development method which includes the stages of needs analysis, system design, implementation, and testing. Data were collected through direct observation of the manual letter archiving process, interviews with system users, and literature studies related to information systems and archiving. The results of the study indicate that this website-based letter archive information system has succeeded in increasing the efficiency of letter archive management. This system allows users to easily store, manage, and search for archived letters. The use of this system also reduces the risk of data loss and speeds up the letter search process. Thus, this information system is expected to be an effective solution in overcoming the problems faced by organizations in managing letter archives.